Utilization of Kaplan Turbine with Variation of Water Discharge of Ciparay River in Stamplat Girang Village, Indragiri Village - Sihombing, Tri Octaviani; Pattipawaej, Olga Catherina (Jurnal Teknik Sipil, 2024)
Stamplat Girang Village has quite large potential for developing micro-hydro power plants using Kaplan turbines, considering the hilly topography and the presence of the Ciparay river. The Ciparay River has quite a large water flow throughout the year. The main objective of this research is the use of the Kaplan Turbine with variations in Ciparay river water discharge. Measurements of water flow velocity and cross-section of the Ciparay river were carried out directly in low rainfall conditions and in high rainfall conditions. The average water flow of the Ciparay river is lowest at low rainfall at 0.22 m3/s and highest at high rainfall at 1.46 m3/s. With an energy height of 2 m, the effective electrical power produced is 6,592 watts in low rainfall conditions and the highest produced is 18,098 watts in high rainfall conditions. The effective electrical power obtained can be directly beneficial to various aspects of the regional government's efforts to assist the development of Stamplat Girang Village in empowerment and environmental development as well as supporting the Indonesian government's efforts to encourage the development of micro hydro energy in achieving sustainable development goals.